Efecto del empadre posparto y postdestete sobre el tamaño y peso de la camada de cuyes - Chauca Francia, Lilia Janine (1992)
Postpartum breeding ia a common practice among guinea pig-producing farmers, even at the commercial level. This is possible because these animals como into heat 2-3 h postpar tum. Available evidence is not conclusive with regard to the advantages and disadvantages of this practice, when com wall with post-weaning mating. This was carried out in order to generate information that would allow for the intention of existing guinea pig production systems, under the hypothesis that breeding postpartum has no effect on litter size and weight both at birth and at weaning. Data on the first two parturitions of 300 females, at La Molina Agricultural Experimental Station, were analyzed. These females were part of a line-breeding selection program carried out at the station, of which 68.3% presented post-partum gestations and 31.7% post-weaning gestations. The four different maternal lines used made up one variable: Peru (18.3% of all females), Andina (27.7%), Inti (25.3%) and Control (ordinary stock) (28.7%). No differences in terms of mating-partum interval, nor in terms of litter size and weight, both at birth and at weaning, were detected at the first parturition. Comparisons between the selected breed lines showed that mating partum interval was shortest (P≤ 0.01) for the Andina line (81.6 ±1.89). The Andina and Control groups presented larger litters at both birth and weaning. Mating system, evaluated in the second parturition, had no effect at litter size at birth or at weaning. Average individual weight at birth was higher (P≤0.01) in offspring from post-weaning gestations (121 ± 12.43 g vs. 135 ± 3.62 g), a difference that was also noted (P≤0.05) at weaning time (P≤0.01). Partum intervals were 68 ± 0.16 and 112 ± 1.67 days in females conceiving post-partum and post-weaning, respectively. There were no effects of mating system within selected lines with respect to litter size or individual birth or weaning weights. When breed lines were compared (independent of mating system), the Peru and Inti lines showed heavier individual birth weights. Some differences were found among lines with respect to parturition intervals.